2007
DOI: 10.1016/j.virol.2007.02.012
|View full text |Cite
|
Sign up to set email alerts
|

The adenovirus E4orf6 E3 ubiquitin ligase complex assembles in a novel fashion

Abstract: The human adenovirus E4orf6 and E1B55K proteins are part of an E3 ubiquitin ligase complex that degrades p53, Mre11 and probably other cellular polypeptides. Our group has demonstrated previously that this complex contains Cul5, Rbx1 and Elongin B and C and is formed through interactions of these cellular proteins with E4orf6. Although this E4orf6 complex is similar in many ways to the cellular SCF and VBC E3 ligase complexes, our previous work indicated that unlike all known Cullin-containing complexes, E4orf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…From studies with cellular ligases, the BC-box motif was identified as (STP)LXXX(CSA)XXX⌽ (29,30). As noted earlier, the HAdV-5 E4orf6 protein contains three functional BC boxes (31,32,45). Our studies on the HAdV-5 BC boxes also showed that the first residue of this motif is not important and that a glycine can replace the hydrophobic residue at the last position.…”
Section: Analysis Of E4orf6 Proteins From Primate Mastadenoviruses (I)supporting
confidence: 61%
See 1 more Smart Citation
“…From studies with cellular ligases, the BC-box motif was identified as (STP)LXXX(CSA)XXX⌽ (29,30). As noted earlier, the HAdV-5 E4orf6 protein contains three functional BC boxes (31,32,45). Our studies on the HAdV-5 BC boxes also showed that the first residue of this motif is not important and that a glycine can replace the hydrophobic residue at the last position.…”
Section: Analysis Of E4orf6 Proteins From Primate Mastadenoviruses (I)supporting
confidence: 61%
“…In our studies on HAdV-5 (HAdV-C), we showed that the E3 ubiquitin ligase complex assembled by E4orf6 and E1B55K (14) requires the presence in E4orf6 of a BC box (in fact, it contains three) (31,32) that enables complex formation with the cellular proteins Cul5, Elongins B and C, and RBX1 before binding to E1B55K, which functions as the major substrate recognition protein (31,32). Formation of this ligase complex was shown to be an important function of E4orf6 during infection, as a BC-box mutant unable to form the complex exhibited the same defective phenotype as that of a mutant lacking E4orf6 entirely (33).…”
mentioning
confidence: 99%
“…The human adenovirus type 5 (Ad5) early region 4 34-kDa product from open reading frame 6 (E4orf6) contains three BC boxes (Blanchette et al, 2004; Cheng et al, 2007, 2011). Although Ad5 E4orf6 forms complex containing Cul5, Elongin BC complex, and Rbx1, Cul5 box is not present in the Ad5 E4orf6 (Harada et al, 2002; Blanchette et al, 2004; Cheng et al, 2011).…”
Section: Viral Ecs-type Ubiquitin Ligasementioning
confidence: 99%
“…Although Ad5 E4orf6 forms complex containing Cul5, Elongin BC complex, and Rbx1, Cul5 box is not present in the Ad5 E4orf6 (Harada et al, 2002; Blanchette et al, 2004; Cheng et al, 2011). Adenoviral protein E1B55K associates with the E4orf6 protein and recognizes substrate to be degraded by ubiquitin–proteasome pathway (Blanchette et al, 2004; Cheng et al, 2007; Luo et al, 2007). This complex is essential for efficient viral replication and some substrates have been identified, including p53 (Moore et al, 1996; Querido et al, 1997; Steegenga et al, 1998; Cathomen and Weitzman, 2000; Nevels et al, 2000; Shen et al, 2001), meiotic recombination 11 (Mre11; Stracker et al, 2002; Blanchette et al, 2004), DNA ligase IV (Baker et al, 2007), integrin α3 (Dallaire et al, 2009), and adeno-associated virus type 5 (AAV5) Rep52 and capsid proteins (Nayak et al, 2008).…”
Section: Viral Ecs-type Ubiquitin Ligasementioning
confidence: 99%
“…Furthermore, no impact of the E1B 55-kDa protein on inhibition of the p53-dependent transcriptional program was detected in a genome-wide comparison of cellular gene expression in normal human cells infected by Ad5 and such a mutant (48). These observations indicate that, while the E1B 55-kDa protein and the E3 ubiquitin ligase in which it serves as the substrate recognition subunit (49)(50)(51)(52) are necessary to prevent accumulation of p53, it is not responsible for inhibition of transcriptional activation (or repression) by p53. This function has been ascribed more recently to the E4 Orf3 protein: expression of p53-responsive genes was reported to be increased in cells infected by a mutant virus null for production of both the E1B 55-kDa and E4 Orf3 proteins compared to those infected by the wild-type virus or an E1B 55-kDa-null mutant (53).…”
Section: The Tumor Suppressor P53 a Master Regulator Of Cellular Resmentioning
confidence: 90%